2008
DOI: 10.2485/jhtb.17.99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Mineral Density and Area of Newly Formed Bone Around Ti-15%Zr-4%Nb-4%Ta Alloy and Ti-6%Al-4%V Alloy Implants

Abstract: Abstract:A newly developed titanium alloy, Ti-15%Zr-4%Nb-4%Ta (Ti15Zr4Nb4Ta), has been shown to have excellent mechanical characteristics, corrosion fatigue strength, anticorrosion, cytocompatibility, and biocompatibility. The purpose of this study was to compare the bone mineral density (BMD) and area of newly formed bone around Ti15Zr4Nb4Ta implants to that around Ti-6%Al-4%V alloy (Ti6Al4V) implants. We inserted 2 types of implants (surface treat of the machine and the blast implant) in New Zealand white ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Measurements can be taken without pretreatment or advanced skills, and the technique is particularly useful for bone density measurements and microstructural analyses of bone tissues. This modality is commonly used in other fields of research [26][27][28] ; in this study, we found that the technique was able to clarify differences in bone microarchitecture among rats subject to oestrogen deficiency, and combined oestrogen-mineral deficiency.…”
Section: D Bone Density Distribution Mapsmentioning
confidence: 56%
“…Measurements can be taken without pretreatment or advanced skills, and the technique is particularly useful for bone density measurements and microstructural analyses of bone tissues. This modality is commonly used in other fields of research [26][27][28] ; in this study, we found that the technique was able to clarify differences in bone microarchitecture among rats subject to oestrogen deficiency, and combined oestrogen-mineral deficiency.…”
Section: D Bone Density Distribution Mapsmentioning
confidence: 56%
“…5) o reabsorción ósea en el hueso cercano al biomaterial implantado (Kuroda et al 1998). Nakada et al (2008) propone el empleo de las aleaciones de titanio de la familia TNTZ para ser empleadas en implantes ortopédicos. Esta familia de aleaciones presenta un bajo módulo elástico, excelente resistencia mecánica, elevada resistencia a la corrosión y están compuestas por elementos biocompatibles.…”
Section: Resistencia Mecánicaunclassified
“…Studies in rabbit animal models showed that fracture in tibia reported lowest bone atrophy and hence better bone remodelling for TNTZ rods and plates as compared to Ti-6Al-4V ELI, and SUS 316L. The diameter of the tibia was increased, and a double wall structure was observed for intramedullary bone when TNTZ were used as rods [60][61][62][63][64][65].…”
Section: Alloys and Coatings Of Tantalum Ti-29nb-13ta-46zr (Tntz)mentioning
confidence: 99%